Update of patient-reported quality-of-life measurement instruments for patients with atopic dermatitis - Huihui LU; Yingxia GAO; Qianying ZHANG; Zhenzhen CAO; Xiaochun LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with the highest disease burden among non-fatal dermatoses. Severe itching and frequent recurrence seriously affect the patients' psychological and social functions, resulting in a significant decline in the patients' quality of life. Using effective measurement instrument to assess the quality of life is an effective way to evaluate the quality of life of AD patients, and to improve patients' care experience and the clinical outcomes. Here, we review the patient-reported quality-of-life measurement instruments, including generic instruments, dermatology-specific instruments, and disease-specific instruments used in AD. The generic instruments can be used to compare the quality of life of patients with AD and non-skin diseases, while the dermatology-specific instruments can be used to compare the quality of life of patients with different skin diseases. Dermatology-specific instruments and disease-specific instruments used in AD may have greater discriminatory power and higher specificity and sensitivity for subtle changes. How to choose the appropriate scale in clinical practice and research depends on the research question and the applicable population.